BIOEFFICACY OF L. SEEDS PSORALEA CORYLIFOLIA AGAINST INCITANT OF SCLEROTIUM ROLFSII, COLLAR ROT OF CHICKPEA (Journal of Plant Disease Sciences, 2017)
Laboratory bioassays were carried out to evaluate the antifungal potential of acetone, chloroform, distilled water, ethanol and methanol extract of Psoralea corylifolia Sclerotium rolfsii (Cicer L. seeds against causing collar rot of chickpea arietinum L.). Different concentrations of solvent extracts (125, 250, 375 and 500 µl) were prepared and their effect against were tested by using poisoned S. rolfsii food technique. Maximum mycelial growth inhibition of the fungal pathogens was observed in methanol extract at 500 µl concentration (98.23%). Methanolic extract was fractioned on thin layer chromatography (TLC) plates using different eluting solvent systems. From all solvent systems, toluene: ethyl acetate: methanol (24:04:02 v/v) separated more number of secondary metabolites from methanol extract of seeds. In TLC-bioautography none of the separated P. corylifolia compound showed prominent activity against the tested fungal pathogen. Antifungal activity of methanol extract seeds clearly indicated that the P. corylifolia inhibition recorded in poison food technique was due to the synergetic effect of most of the compounds from the extract. The present study concludes that methanol extract of seeds possess antifungal activity and can be used for P. corylifolia management of . S. rolfsii
Keywords: Psoralea corylifolia, S. rolfsii, bioefficacy